An educational intervention’s effect on healthcare professionals’ attitudes towards pharmacovigilance - Jha, Nisha (Australas Med J, 2014)
BACKGROUND: Pharmacovigilance concerns the detection, assessment, understanding, and prevention of adverse effects or any other drug-related problems. Consumer pharmacovigilance is the involvement of consumers in adverse drug reaction (ADR) reporting. Assessing healthcare professionals’ (HCPs) knowledge of and attitude towards pharmacovigilance and consumer pharmacovigilance is integral to strengthening adverse drug reaction reporting systems. AIMS: To study knowledge of and attitude towards pharmacovigilance and consumer pharmacovigilance among HCPs from KIST Medical College, Lalitpur, Nepal, and to plan an appropriate educational intervention to address deficiencies noted. METHOD: The study was conducted from February 2013 to December 2013 at KIST Medical College using a self-administered, pretested, structured questionnaire. The maximum possible scores for knowledge, attitude, and total were 100, 95, and 195, respectively. Baseline knowledge and attitude were studied. Two months after the questionnaire, an intervention that used a combination of methods about pharmacovigilance and consumer pharmacovigilance was undertaken. Knowledge and attitudes were studied immediately after the intervention. Scores before and after the intervention were compared using Wilcoxon signed-rank test. RESULTS: A total of 105 HCPs participated. The median (interquartile range) knowledge, attitude, and total scores before the intervention were 56 (7), 72 (9), and 127 (16), respectively. After the intervention the scores increased significantly to 72 (8), 75 (11.5), and 146 (16.5) (p<0.001), respectively. CONCLUSION: The intervention was effective in improving HCPs’ knowledge of and attitude towards pharmacovigilance and consumer pharmacovigilance. More studies on this topic among HCPs at other institutions and in the community are required.